2018
DOI: 10.3906/sag-1803-135
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic thiol-disulfide homeostasis is disturbed in hepatitis B virus-related chronic hepatitis and liver cirrhosis

Abstract: Background/aim: Thiol-disulfide homeostasis is an important antioxidant defense mechanism. This study was conducted to investigate dynamic thiol-disulfide homeostasis in patients with hepatitis B virus-related chronic hepatitis and liver cirrhosis.Materials and methods: Seventy-one treatment-naive patients with chronic hepatitis B (CHB), 50 patients with hepatitis B virusassociated liver cirrhosis, and 45 healthy controls were included in the study. Serum total and native thiol concentrations and serum disulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…This increased oxidative stress in CHC may be caused by chronic inflammation and continuous production of ROS in HCV‐infected cells 16 . Similarly, researchers have observed that the DTDH shifted to the DS side in other infectious diseases such as chronic hepatitis B 9 and Crimean‐Congo haemorrhagic fever 10 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This increased oxidative stress in CHC may be caused by chronic inflammation and continuous production of ROS in HCV‐infected cells 16 . Similarly, researchers have observed that the DTDH shifted to the DS side in other infectious diseases such as chronic hepatitis B 9 and Crimean‐Congo haemorrhagic fever 10 …”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported that impaired DTDH plays a role in the pathogenesis of various diseases such as chronic hepatitis B, 9 Crimean‐Congo haemorrhagic fever, 10 diabetes 11 and familial Mediterranean fever 12 . However, DTDH, an alternative indicator of oxidative stress, has not yet been investigated using the new method in HCV‐infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that increased OS may have a role in the pathogenesis of idiopathic recurrent AP. Many recent studies have reported on thiol levels and thiol/SS homeostasis in patients with chronic hepatitis, ulcerative colitis, and coronary artery disease (14)(15)(16)(17); however, till date, only one study has been conducted on patients with AP (18). To the best of our knowledge, no studies have been conducted with regard to IMA.…”
Section: Introductionmentioning
confidence: 99%
“…7 While the thiol side of the thiol-disulfide system has been measured since 1979, it was only in 2014 that Erel and Neselioglu developed a reliable way to measure the level of both components of this system quickly and cheaply. 8 Previous studies have reported that impaired DTDH plays a role in the pathogenesis of various diseases such as chronic hepatitis B, 9 Crimean-Congo hemorrhagic fever, 10 diabetes 11 and familial Mediterranean fever. 12 However, DTDH, an alternative indicator of oxidative stress, has not yet been investigated using the new method in HCV-infected patients.…”
Section: Introductionmentioning
confidence: 99%